Stories in Conversation - Hofer, Roberta Senner (Kansas Working Papers in Linguistics, 1991)
Because conversational stories can be used for different purposes, they enter conversations in different ways. Sometimes they have a preface, sometimes not; sometimes a story fits smoothly into the ongoing talk, but other times it changes the topic. Observations such as these led me to the formulation of three major types of stories in conversation. While they share the same overall structure, each type has distinctive features. The features and story entry variations are described in this paper.